Revisiting: "A pre-post study of a multi-country scale up of resuscitation training of facility birth attendants: does helping babies breathe training save lives?" - Sara Berkelhamer; Nalini Singhal (BMC, 2019)
Abstract Background Helping Babies Breathe (HBB) is a low cost, skills-based neonatal resuscitation education program designed specifically for use in low resource settings. Studies from Tanzania, India and Nepal have demonstrated that HBB training results in decreased rates of fresh still birth and/or neonatal mortality. However, less is known regarding the impact of training on neonatal mortality at a population level. Bellad et al. utilized (BMC Pregnancy Childbirth. 2016;16 (1):222) utilized population based registries to evaluate outcomes before and after training of facility birth attendants. Their study entitled "A pre-post study of a multi-country scale up of resuscitation training of facility birth attendants: Does Helping Babies Breathe training save lives?" suggested facility based training was not associated with consistent improvements in neonatal mortality on a population level. Discussion Combining outcomes from three diverse settings may have under-estimated the impact of HBB training. We remain concerned that the modest benefits observed in the Kenyan site were lost with compiling of data. Summary The statement that HBB "was not associated with consistent improvements in mortality" may lead to the mistaken conclusion that improvements in neonatal mortality were not seen, when in fact, they were in selected cohorts. With numerous studies demonstrating potential for reduced neonatal mortality as a result of HBB training, we encourage interpretation of these findings in the context of local care.